2017
DOI: 10.1038/s41598-017-05945-2
|View full text |Cite
|
Sign up to set email alerts
|

Generation of clade- and symbiont-specific antibodies to characterize marker molecules during Cnidaria-Symbiodinium endosymbiosis

Abstract: The endosymbiosis between cnidarians and dinoflagellates is responsible for the formation of coral reefs. Changes in molecules have been identified during the process of cnidaria-Symbiodinium endosymbiosis. However, the complexity of the molecular interaction has prevented the establishment of a mechanistic explanation of cellular regulation in this mutualistic symbiosis. To date, no marker molecules have been identified to specifically represent the symbiotic status. Because the endosymbiotic association occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…The other encodes a sucrose-phosphate synthase family protein SPS4 , which might be related to photosynthetic sucrose synthesis. In the cnidarian-algal symbiosis, it is suggested that sugar, more specifically glucose, is an important component for not only the supply of photosynthesized carbohydrates from symbiont to host (Burriesci et al 2012) but also for the recognition of symbionts by the host (Takeuchi et al 2017; Huang et al 2017). Our results raise a possibility that cytosolic sugar metabolism and Golgi apparatus-mediated glycosylation of proteins and/or cell wall components may be susceptible to stress and damage when symbionts are exposed to heat in hospite (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other encodes a sucrose-phosphate synthase family protein SPS4 , which might be related to photosynthetic sucrose synthesis. In the cnidarian-algal symbiosis, it is suggested that sugar, more specifically glucose, is an important component for not only the supply of photosynthesized carbohydrates from symbiont to host (Burriesci et al 2012) but also for the recognition of symbionts by the host (Takeuchi et al 2017; Huang et al 2017). Our results raise a possibility that cytosolic sugar metabolism and Golgi apparatus-mediated glycosylation of proteins and/or cell wall components may be susceptible to stress and damage when symbionts are exposed to heat in hospite (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that lectin proteins capable of binding the glucose moiety might be involved in the recognition of Symbiodiniaceae symbionts by the host coral Acropora tenuis (Takeuchi et al 2017). Furthermore, a glycoprotein was characterized as the first Symbiodiniaceae protein and was localized at the cell surface, expressed exclusively when the symbiont was colonized within the host (Huang et al 2017). In the HIB process, the altered transport rate of degraded metabolites to the host cytosol may work as a negative feedback signal for the subsequent decrease of metabolite flow (Davy et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous works, we successfully isolated SGCs from E. glabrescens and studied the endosymbiosis relationship between stony corals and dinoflagellates [6,12,14]. We now wanted to establish a new model system using octocorals as an animal model to study the endosymbiotic relationship between octocorals and dinoflagellates.…”
Section: Incubation Of Octocorals In a High-salinity Solution Increased The Amount Of Sgcs Released From The Tentaclesmentioning
confidence: 99%
“…Furthermore, we used SGCs as an antigen to generate antibodies and produced a new monoclonal antibody that specifically recognizes clade C (now renamed Cladocopium) [13] symbionts, but not their free-living counterparts or other Symbiodiniacea. The monoclonal proteins recognizable by the antibody are symbiotic markers for Cladocopium symbionts, whose expression levels vary depending on the health status of corals [14]. Accordingly, SGC membranes may regulate the stability of the host coral and dinoflagellates.…”
Section: Introductionmentioning
confidence: 99%